2021
DOI: 10.3762/bjoc.17.189
|View full text |Cite
|
Sign up to set email alerts
|

The PIFA-initiated oxidative cyclization of 2-(3-butenyl)quinazolin-4(3H)-ones – an efficient approach to 1-(hydroxymethyl)-2,3-dihydropyrrolo[1,2-a]quinazolin-5(1H)-ones

Abstract: A regioselective method for the synthesis of 1-(hydroxymethyl)-2,3-dihydropyrrolo[1,2-a]quinazolin-5(1H)-ones – close structural analogs of naturally occurring vasicinone alkaloids – is described. The procedure is based on PIFA-initiated oxidative 5-exo-trig cyclization of 2-(3-butenyl)quinazolin-4(3Н)-ones, in turn prepared by thermal cyclocondensation of the corresponding 2-(pent-4-enamido)benzamides. The products obtained have a good natural product likeness (NPL) score and therefore can be useful for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 58 publications
0
4
0
1
Order By: Relevance
“…Vaskevych et al 124 detailed an oxidative and regioselective PIFA-mediated synthetic methodology for the synthesis of dihydropyrroloquinazolinones 120a–l , structural analogues of vasicinone alkaloids, derived from quinazolinones 119a–l . All quinazolones 119a–l underwent 5- exo-trig cyclization, resulting in the desired products 120a–l obtained with yields ranging from 75–83% (Scheme 48).…”
Section: Pifa In Organic Synthesismentioning
confidence: 99%
“…Vaskevych et al 124 detailed an oxidative and regioselective PIFA-mediated synthetic methodology for the synthesis of dihydropyrroloquinazolinones 120a–l , structural analogues of vasicinone alkaloids, derived from quinazolinones 119a–l . All quinazolones 119a–l underwent 5- exo-trig cyclization, resulting in the desired products 120a–l obtained with yields ranging from 75–83% (Scheme 48).…”
Section: Pifa In Organic Synthesismentioning
confidence: 99%
“…The same authors described a selective synthesis of 1-(hydroxymethyl)-2,3-dihydropyrrolo[1,2-a]quinazolin-5(1H)ones 32 based on the PIFA-initiated oxidative 5-exo-trig cyclization of 2-(3-butenyl)quinazolin-4(3H)-ones 22 (Scheme 8). [77] Screening of reaction conditions revealed that the reaction proceeds efficiently using 2.…”
Section: R E V I E W T H E C H E M I C a L R E C O R Dmentioning
confidence: 99%
“…The same authors described a selective synthesis of 1‐(hydroxymethyl)‐2,3‐dihydropyrrolo[1,2‐ a ]quinazolin‐5(1 H )‐ones 32 based on the PIFA‐initiated oxidative 5‐ exo‐trig cyclization of 2‐(3‐butenyl)quinazolin‐4(3 H )‐ones 22 (Scheme 8). [77] Screening of reaction conditions revealed that the reaction proceeds efficiently using 2.5 equiv. of PIFA in a trifluoroethanol (TFEA) solution at 0 °C for 24 h. The oxidative heterocyclization of quinazolinones 22 can occur by two pathways (Scheme 8).…”
Section: Cyclizations Of 2‐alkenyl(alkynyl) Functionalized Quinazolin...mentioning
confidence: 99%
“…Не менш значимими об'єктами для біомедичних досліджень видаються ангулярно-анельовані похідні піроло[1,2-a]хіназолінону, серед яких знайдені перспективні депресанти центральної нервової системи (IV) [20], седативні агенти (V) [21] та інгібітори бромодоменів білків PB1 та SMARCA 4 (VI) [22][23] Нещодавно [24] ми розробили зручний регіоселективний метод синтезу нового типу сірковмісних піроло[1,2-a]хіназолінонових сполук -1-(арилсульфанілметил)-2,3дигідропіроло[1,2-a]хіназолін-5(1Н)-онів 1, який ґрунтувався на електрофільній циклізації відповідних 2-(3-бутеніл)хіназолінонів 2 під дією арилсульфенілхлоридів 3 у розчині нітрометану в присутності літію перхлорату як «допінг-добавки» (схема 1). Зазначимо, що сполуки типу 1 є представниками небагато чисель-них 1-функціоналізованих піроло[1,2-a]хіназолінонів [25]. Їх незаміщений по пірольному ядру аналог був виділений із плодів японського каштана (Castanecrenata) у 2015 році [26].…”
Section: предметом представленої роботи є дослідження антиоксидантних...unclassified